(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
The text is intended to be a manifest, in epistolary form, about confluences between research, art and life, pondering about the academy and the academic relations established between advisor and advisee, aiming to shed light on how one investigate and how one can instigate to investigate, observing the processes experienced towards the production as a doula accompanies a gestation, with such accuracy and generosity that can surpass norms and traditional ways to face a research and their outcomes.